(untitled) (Itinera, 2023)
This paper inquires what kind of art best enhances what Jacques Rancière means by "politics". It argues that performance (theatre) and other types of artistic manifestations that include a performative component achieve what Rancière considers political equality. The paper argues on two fronts. First, it argues that artistic manifestations should not be understood as a special event, as understood in the traditional form of "ritual". Secondly, the paper takes this discussion to the question of the use of space in artistic manifestations. It is argued that performances should make a differential use of space, constituting spaces of categorical confusion, called thresholds, in order to better enhance Rancière’s politics.